Modulation of colonic function in irritable bowel syndrome rats by electroacupuncture at ST25 and the neurobiological links between ST25 and the colon - Zhang, Lili; Yu, Cheng; Chen, Biwei; Chao, Yuqiao; Zhang, Haiyan; Zhao, Qinyu; Yang, Kaiwei; Zhang, Yujiao; Chen, Shaozong (Frontiers in Neuroscience, 2022)
Irritable bowel syndrome (IBS) is a chronic functional gastrointestinal disease characterized by abdominal pain and defecation disorders. A large number of studies have shown that acupuncture therapy has a positive therapeutic effect on irritable bowel syndrome (IBS), and ST25 is one of the main points. However, in previous studies, ST25 was mostly used in conjunction with other acupoints. To observe the therapeutic effect of electroacupuncture at ST25 alone on IBS and the neurobiological mechanism of ST25 associated with the colon, we conducted this experiment. This study consists of two parts. In the first part, we observed the effect of electroacupuncture at ST25 on visceral pain threshold and slow-wave discharge of the colon in IBS model rats. In the second part, we explored the neurobiological mechanism of ST25 associated with the colon by neural tracer technique. Results showed that: (1) Electroacupuncture at ST25 can improve the visceral pain threshold of IBS rats, reduce visceral hypersensitivity, restore normal slow wave frequency and rhythm of the colon, and improve colon function; (2) The close neuroanatomical connection between the ST25 and the colon: In the dorsal root ganglion, ST25 is similar in innervation to the colon, mainly in the T8-L1 segment (T11 is the overlapping peak segment), while the presence of double-labeled positive neurons in a part of the dorsal root ganglion; retrogradely labeled motor neurons at ST25 were observed in the anterior horn of the spinal cord; retrogradely labeled sympathetic postganglionic neurons at ST25 were observed in the sympathetic nerve chain. These findings suggested that the dorsal root ganglion and the dorsal horn of the spinal cord are important targets for electroacupuncture ST25 to reduce visceral hypersensitivity in IBS rats. The sympathetic ganglion is one of the important sites for ST25 to regulate intestinal motility, and the regulation of intestinal motility by ST25 in IBS rats may be the result of the joint action of the sympathetic circuit and the vagal circuit. The neurobiological mechanism of ST25 action on IBS rats will be further investigated in the future by combining related techniques such as pseudorabies virus, optogenetics, calcium imaging and electrophysiology.